2011
DOI: 10.1186/1752-1947-5-304
|View full text |Cite
|
Sign up to set email alerts
|

"Giant R wave" electrocardiogram pattern during exercise treadmill test: A case report

Abstract: IntroductionThe exercise treadmill test is widely used in the evaluation of patients with suspected or known coronary artery disease. The typical ischemic response used to be ST-segment depression.Case presentationWe describe a case of a 51-year-old Caucasian man with an unusual ischemic response during the exercise treadmill test: a "giant R wave" electrocardiogram pattern as a manifestation of hyperacute ischemia that resolved with sublingual nitroglycerin. Coronary catheterization showed a severe stenosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Electrocardiographic leads with ST-segment elevation have a good prediction value for the site of hypoperfusion and the same observation was valid in our case (31). The particular ECG aspect of giant R and monophasic QRS-ST complex may be rarely observed, except from variant angina, in acute myocardial infarction and after percutaneous transluminal coronary angioplasty (32).…”
Section: Discussionsupporting
confidence: 86%
“…Electrocardiographic leads with ST-segment elevation have a good prediction value for the site of hypoperfusion and the same observation was valid in our case (31). The particular ECG aspect of giant R and monophasic QRS-ST complex may be rarely observed, except from variant angina, in acute myocardial infarction and after percutaneous transluminal coronary angioplasty (32).…”
Section: Discussionsupporting
confidence: 86%
“…3 Giant R-wave syndrome is uncommon and observed primarily in the hyperacute phase of myocardial infarction, variant angina, and after percutaneous transluminal coronary angioplasty or experimental coronary artery ligation. 4 Giant R-wave syndrome reflects the presence of a large area of transmural myocardial ischemia and predicts ventricular fibrillation, accounting for high in-hospital mortality. Aizawa and colleagues 5 reported that this ECG pattern was significantly more prevalent among the selected population with STEMI complicated by ventricular tachycardia (48.0%) compared with the control population of uncomplicated STEMI (4.1%).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has also been described as a “lambda-like” pattern (J waves accompanied by ST-segment elevation) . Giant R-wave syndrome is uncommon and observed primarily in the hyperacute phase of myocardial infarction, variant angina, and after percutaneous transluminal coronary angioplasty or experimental coronary artery ligation . Giant R-wave syndrome reflects the presence of a large area of transmural myocardial ischemia and predicts ventricular fibrillation, accounting for high in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The “giant R wave” of acute myocardial ischemia has previously been reported in patients with acute myocardial infarction [ 3 - 5 ], in variant (Prinzmetal) angina [ 6 ], during exercise treadmill stress test [ 7 - 8 ], in the setting of percutaneous transluminal coronary angioplasty [ 9 ], and following coronary artery ligation in dogs [ 2 ]. Giant R waves, to our knowledge, have not yet been reported in the setting of unstable angina.…”
Section: Discussionmentioning
confidence: 99%